An Overview of US Blueberry Production, Trade, and Consumption, with Special Reference to Florida - Edward A. Evans; Fredy H. Ballen (EDIS, 2014)
This 8-page fact sheet provides updated information about the recent trends in blueberry production, consumption, and trade for the US market. Current and future short-term trends are discussed. Price analysis at the wholesale level for selected markets on the US East Coast (New York City) and US West Coast (Los Angeles) are presented. Also, the national average retail prices for conventional and organic blueberries are presented. Written by Edward A. Evans and Fredy H. Ballen, and published by the UF Department of Food and Resource Economics, October 2014.